Therapeutic role of Cousinia thomsonii in ameliorating the oxidative stress and inflammation: A comprehensive in vitro and in vivo investigation - Bilal Ahmad Reshi; Asif Amin; Umer Majeed; Mushtaq Ahmad Mir; Nasreena Bashir; Raies A. Qadri; Showkat Ahmad Ganie (PLoS ONE, 2026)
The present study evaluated the antioxidant and anti-inflammatory properties of an edible medicinal herb, Cousinia thomsonii (CT), commonly known as Thomson’s thistle. Preliminary investigations such as DPPH assay, lipid peroxidation estimation, reducing power assessment, hydroxyl radical scavenging activity, and plasmid DNA damage assessment revealed that ethyl-acetate extract of the plant exhibited significantly higher antioxidant potential compared to the methanolic extract. We further evaluated the antioxidant potential of ethylacetate extract of Cousinia thomsonii in model cell systems. Using DCFDA staining, our results showed that ethyl acetate extract of this herb alleviated H 2 O 2 -induced oxidative stress in HepG2 cells. Further, the extract protected these cells from H 2 O 2 -induced cell death as demonstrated by PI/DAPI staining-based cell viability assays. These data were further substantiated by the cleavage status of PARP as evaluated by immunoblotting which pointed at the rescue of HepG2 cells from H 2 O 2 induced cell death. Inhibition of NO release, corroborated by the downregulation of iNOS, also confirmed the effect of the extract in SNP-induced NO stress. Additionally, co-treatment with different concentrations of the extract led to the upregulation of Nrf2, the master regulator of oxidative stress, while dose-dependently suppressing LPS-induced TNF-α, IL-1β, and IL-6 expression in THP-1 cells.The in vivo anti-inflammatory activity of Cousinia thomsonii was further assessed through inhibition of paw edema formation and histopathological analysis of paw tissue. Taken together, these findings demonstrate that the ethyl acetate extract of CT exhibit potent antioxidant and anti-inflammatory effects in both in vitro and in vivo models, supporting its potential therapeutic application.